Two new species of Paraehlersia San Martín, 2003 (Polychaeta, Syllidae) from the Atlantic Coast of South America - Fukuda, Marcelo Veronesi; Centurión, Romina; de Matos Nogueira, João Miguel; San Martín, Guillermo (Zootaxa, 2012)
Paraehlersia San Martín, 2003 is reported for the first time for the Atlantic coast off South America based on specimenscollected off Brazil and Argentina. The specimens belong to two new species, which are herein described. Paraehlersialongichaetosa sp. nov., is characterized by having spiniger-like chaetae with long blades, up to 120μm in length, bidentateanterior falcigers, with relatively coarse subdistal tooth, bidentate dorsal simple chaetae, with teeth about same size, andsubdistally irregularly inflated aciculae, apparently hollow, with acute tip. Paraehlersia martapolae sp. nov., has spiniger-like chaetae with shorter blades, up to 82μm in length, bidentate falcigers, with thin subdistal tooth, distally irregularlyrounded dorsal simple chaetae, and aciculae subdistally bent at almost right angle, sometimes with apparently flattenedtop. These new species are compared to their most similar congeners. Additionally, a table summarizing relevant morphological traits of all currently known species of Paraehlersia is included.